WOMEN INDEPENDENCE IN JANE AUSTEN’S SENSE AND SENSIBILITY AS A FEMINISM STUDY - Myta Kusumawardhani; Endang Yuliani Rahayu (Dinamika Bahasa dan Budaya, 2020)
This research paper entitled Women Independence in Jane Austen’s Sense and Sensibility as a Feminism Study. This research paper aimed to show the form of women independence of Elinor Dashwood and Marianne Dashwood as the main characters in Sense and Sensibility novel. This research is using feminist critical approach and applies Simone de Beauvoir’s theory with her book The Second Sex that was published in 1949. This research used qualitative research methods from which the data are taken from books and online sources. Data is classified into main data which is taken from the book itself and supporting data which is taken from online sources that related to this paper. Beside analyzing the forms of women independence, the researcher also analyzed the causes of women independence and the effects of women independence towards the main characters. The novel presents the independence of thought and behavior of women in the 19th century. After all data have been collected and analyzed, it concludes that the causes of the independence of the main characters is their parents, the forms of their independence is Elinor and Marianne Dashwood can prove that they have a good attitude, good knowledge and ability in the world of art although they are just from the middle social class and the effects is they have a positive and negative effect of their independence and get some obstacles of it. However, after overcoming all their conflicts they finally found what they really wants in life and they can live happily.